The occupational exposure of dermatology nurses to polycyclic aromatic hydrocarbons – evaluating the effectiveness of better skin protection - Scheepers, Paul TJ; van Houtum, Jeanette; Anzion, Rob BM; Champmartin, Catherine; Hertsenberg, Selma; Bos, Rob P; van der Valk, Pieter (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'We studied the uptake of polycyclic aromatic hydrocarbons (PAH) in nurses who apply ointments containing coal tar to patients and investigated the effectiveness of skin protection methods. ' ' METHODS ': 'We determined gas-phase PAH on XAD-2 and particle-associated PAH on filters. We also used pads to determine PAH on the skin. Pyrene and benzo(a)pyrene were analyzed by gas chromatography/mass spectrometry and gas chromatography/tandem mass spectrometry; their respective urinary metabolites 1-hydroxypyrene and 3-hydroxybenzo(a)pyrene were analyzed using high performance liquid chromatography with fluorescence detection. ' ' RESULTS ': 'We ruled out the inhalation of airborne pyrene and benzo(a)pyrene as the sources of PAH exposure. However, substantial amounts of pyrene and benzo(a)pyrene were observed on the hands of the nurses (median 33.0 and 16.4 ng/cm2, respectively). Excretion of urinary 1-hydroxypyrene indicated an increased uptake of pyrene in 8 out of 12 nurses. We asked 35 nurses to perform a treatment with gloves followed by a second treatment without gloves. The use of gloves changed the excretion of 1-hydroxypyrene by -0.58 μmol (range -5.1–1.0 μmol), corresponding to a median reduction of 51.5% (P<0.001). Based on this finding, a new protocol was adopted, involving the permanent use of vinyl gloves and Tyvek sleeves. The effectiveness of this protocol was tested against pre-existing work practices and showed a 97% reduction in skin contamination with pyrene and benzo(a)pyrene, and a lowering in urinary excretion of 1-hydroxypyrene of 57%. ' ' CONCLUSION ': 'Protecting the skin more stringently reduced pyrene and benzo(a)pyrene contamination of the hands, and lowered urinary excretion of 1-hydroxypyrene.
Keywords: BaP; benzo[a]pyrene; biological monitoring; coal tar; dermatology nurse; glove; nurse; occupational exposure; PAH; polycyclic aromatic hydrocarbon; PYR; pyrene; skin absorption; skin protection; urinary excretion